Relationship between Family and Myopia: Based on the Jiangsu School Student Myopia Study - Xiyan Zhang; Wenyi Yang; Jie Yang; Wei Du; Yao Xiang; Xin Wang; Chao Huang; Yan Wang; Fengyun Zhang (Journal of Ophthalmology)
Purpose. This study aims to increase our understanding of the relationship between family and myopia in Chinese children. Methods. Students had a physical examination and were required to provide the necessary demographic information. Children and their guardians from different family types were required to fill in a questionnaire concerning myopia factors. Results. In this study, the prevalence of myopia in enrolled students aged 6–17 is 55.5%. The proportion of the nuclear family, extended family, single-parent family, and left-behind family is 40.6%, 43.7%, 11.1%, and 4.6%, respectively. Myopia rates from different family types by the order (nuclear family, extended family, single-parent family, and left-behind family) are 60.0%, 52.0%, 54.7%, and 50.9% taking on a decreasing trend, which shows an opposite trend comparing with elevated blood pressure, dental caries, and obesity. The interaction effect of the family type and region, physical examination, lifestyle (including diet habits, near work, outdoor activities, and sleep), and types of lamps and whether scolded by parents can have a significant impact on myopia. For primary school students (grade: 1–5), the prevalence of myopia in the nuclear family was a bit higher than that of myopia in the left-behind family, but for children in junior and senior high schools, both prevalences stayed similar. Conclusions. In this study, education pressure and time outdoors are still at play, and this kind of effect shows different phenomena in different families. Therefore, previous interventions would still work, and then the most critical challenge would be to ensure that left-behind children completed more schooling.